2018
DOI: 10.1038/s41598-018-19204-5
|View full text |Cite
|
Sign up to set email alerts
|

Cilia-related protein SPEF2 regulates osteoblast differentiation

Abstract: Sperm flagellar protein 2 (SPEF2) is essential for motile cilia, and lack of SPEF2 function causes male infertility and primary ciliary dyskinesia. Cilia are pointing out from the cell surface and are involved in signal transduction from extracellular matrix, fluid flow and motility. It has been shown that cilia and cilia-related genes play essential role in commitment and differentiation of chondrocytes and osteoblasts during bone formation. Here we show that SPEF2 is expressed in bone and cartilage. The anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 40 publications
1
21
0
Order By: Relevance
“…67 A deficiency for cilia-related protein SPEF2 results in osteoblast differentiation defects. 68 In this study, we found that HH and WNT/β-catenin signaling is inverted in conditions of the primary cilia in Dhcr7 −/− and Insig1/2 cKO mice during intramembranous ossification. While both WNT/β-catenin and HH signaling pathways are essential for endochondral ossification as well as for the differentiation and maturation of cultured osteoblasts, 36 previous mouse genetic studies suggest that WNT/β-catenin signaling may be more dominant than HH signaling for osteogenesis in intramembranous ossification during skull formation.…”
Section: Discussionmentioning
confidence: 56%
“…67 A deficiency for cilia-related protein SPEF2 results in osteoblast differentiation defects. 68 In this study, we found that HH and WNT/β-catenin signaling is inverted in conditions of the primary cilia in Dhcr7 −/− and Insig1/2 cKO mice during intramembranous ossification. While both WNT/β-catenin and HH signaling pathways are essential for endochondral ossification as well as for the differentiation and maturation of cultured osteoblasts, 36 previous mouse genetic studies suggest that WNT/β-catenin signaling may be more dominant than HH signaling for osteogenesis in intramembranous ossification during skull formation.…”
Section: Discussionmentioning
confidence: 56%
“…This previous study proposed that the PCD-like phenotypes could be caused by a missense mutation in exon 3 of mouse Spef2 , while a stop-gain mutation at the C-terminus could be responsible for the spermatogenic defects 20. Similarly, ciliary abnormalities leading to bone growth defects and PCD-like symptoms were observed in the mice with a stop codon located after the Spef2 exon 2 23. Both of these PCD-associated Spef2 mutations in mice affected the N-terminus CH domain involved in regulating ciliary function (online supplementary figure 2).…”
Section: Discussionmentioning
confidence: 98%
“…Mutations at different sites within SPEF2 produced disparate phenotypes. Depletion mutations at the N‐terminus caused hydrocephalus, growth retardation and an early death phenotype . A nonsense mutation in exon 28 caused PCD in mice.…”
Section: Discussionmentioning
confidence: 99%